Social learning environments - Gomez Alvarado, H. (2016)
This article presents a new training model that uses social networks integrated in a Moodle environment through a plug-in called Glesone. The plug-in is a piece of software built to provide the moodle platform with possibilities of facebook-style comments. This feature, more than solely appearance, allows the possibility to evolve from virtual learning environments to social networks of learning. This change implies several methodological considerations organized in a reference model. The software is used in an Ecuadorian university. In this paper, some results are presented and as an early conclusion we found that comments per theme format offer the most suitable learning environment due to the organization and structure of the content and the class.